URINARY INCONTINENCE AND EXERCISE: KINESIOLOGICAL DESCRIPTION OF AN INTERVENTION PROPOSAL - Caetano,Aletha Silva (2019)
ABSTRACT Introduction Research shows that symptoms of urinary incontinence are common among women who engage in physical activity. Objective To conduct a kinesiological analysis of specific exercises for the pelvic floor muscles (PFM), proposing correspondences of these postures through resistance exercises. Methods This research project is of a descriptive nature with level of evidence V. Videos and photos were taken to obtain an image for the collection of data based on the accomplishment of the specific postures. Results The kinesiological study revealed that the muscles involved in the postures of exercises targeting the prevention of urinary incontinence beyond those specific to the pelvic floor were: trunk flexors; spinal erector; adductors and hip extensors. The resistance exercises corresponding to these positions in bodybuilding apparatus were the machine hack squat; sitting adductor exercises; sitting abductor exercises; the smith machine squat and the free squat or machine squat. Conclusion This study showed that it is possible to construct correspondence between exercises for the pelvic floor muscles and resistance exercises with bodybuilding equipment and free weights. A new strategy is suggested for the physical education professional, based on resistance exercises: taking a coadjuvant approach to the treatment and prevention of urinary incontinence during physical and sports exercises. Level of evidence V, Case series.